Mechanisms of physiological and pathological cardiac hypertrophy - Nakamura, Michinari; Sadoshima, Junichi (Nature reviews cardiology, 2018)
Cardiomyocytes exit the cell cycle and become terminally differentiated soon after birth. Therefore, in the adult heart, instead of an increase in cardiomyocyte number, individual cardiomyocytes increase in size, and the heart develops hypertrophy to reduce ventricular wall stress and maintain function and efficiency in response to an increased workload. There are two types of hypertrophy: physiological and pathological. Hypertrophy initially develops as an adaptive response to physiological and pathological stimuli, but pathological hypertrophy generally progresses to heart failure. Each form of hypertrophy is regulated by distinct cellular signalling pathways. In the past decade, a growing number of studies have suggested that previously unrecognized mechanisms, including cellular metabolism, proliferation, non-coding RNAs, immune responses, translational regulation, and epigenetic modifications, positively or negatively regulate cardiac hypertrophy. In this Review, we summarize the underlying molecular mechanisms of physiological and pathological hypertrophy, with a particular emphasis on the role of metabolic remodelling in both forms of cardiac hypertrophy, and we discuss how the current knowledge on cardiac hypertrophy can be applied to develop novel therapeutic strategies to prevent or reverse pathological hypertrophy.